2012
DOI: 10.1016/j.otsr.2012.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Autologous chondrocyte implantation for traumatic full-thickness cartilage defects of the knee in 14 patients: 6-year functional outcomes

Abstract: IV, prospective therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…A consensus was reached on the explicit classification of short-, mid-, and long-term follow-up. Based on current literature terminology for cartilage repair in the human knee, short term was defined to be follow-up from 1 to 4 years, [19][20][21][22][23] with mid-term defined as 5-8 years, [24][25][26][27][28] and long term as greater than 9 years. 15,17,[29][30][31][32][33][34] Articles in question of inclusion and exclusion criteria were discussed among the authors to reach a consensus decision.…”
Section: Methodsmentioning
confidence: 99%
“…A consensus was reached on the explicit classification of short-, mid-, and long-term follow-up. Based on current literature terminology for cartilage repair in the human knee, short term was defined to be follow-up from 1 to 4 years, [19][20][21][22][23] with mid-term defined as 5-8 years, [24][25][26][27][28] and long term as greater than 9 years. 15,17,[29][30][31][32][33][34] Articles in question of inclusion and exclusion criteria were discussed among the authors to reach a consensus decision.…”
Section: Methodsmentioning
confidence: 99%
“…Second, severe surgical trauma caused by too many defects (4 defects) in both legs might have negatively influenced osteochondral regeneration and articular function recovery3738. Third, appropriate postoperative care and rehabilitation, which is difficult to guarantee in a large animal model, might impose another important negative factor394041. Finally, individual differences among animals might also influence ultimate repair outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the differentiation of stem cells before transplantation is a strategy to lock the mesenchymal stem cells into the desired differentiation state, that is, chondrocytes (Dickhut et al, 2009). Earlier in vitro studies have revealed that transforming growth factor beta (TGF-b), Ascorbate 2 phosphate (A-2P), and dexamethasone containing media support the synthesis of proteoglycans (Johnstone et al, 2006;Chubinskaya et al, 2011;Viste et al, 2012;Ude et al, 2014).…”
Section: Discussionmentioning
confidence: 99%